Preeclampsia and the systemic inflammatory response. - Redman, C; Sargent, I (2004)
Normal pregnancy is associated with a systemic inflammatory response. The response is exacerbated in preeclampsia and can account for its clinical features. Many of the physiologic changes of normal pregnancy are part of an acute-phase reaction, which is generated by an inflammatory response. The placenta is the proximal cause of these problems. There are several possible placental factors that may evoke the inflammatory responses that currently are being investigated. The special susceptibility of obese women, or those with diabetes or chronic hypertension, to preeclampsia is explained by the chronic systemic inflammatory responses that these women have. The clinical implications of these concepts are discussed.